2021
DOI: 10.1111/ijcs.12665
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotions in consumer brand relationship: A review and future research agenda

Abstract: Emotions have a compelling and strong effect on individuals actions and behaviours. They are elicited in consumers during the decision‐making process through brand‐related stimuli. Negative emotions towards a brand can translate directly into actions against it, for instance, propagating negative word of mouth, avoidance and vengeance. Although scholars have conducted consumer–brand relationship (CBR) research for over 20 years, our understanding of negative emotions is still limited. Research in the consumer–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 161 publications
(378 reference statements)
6
76
0
Order By: Relevance
“…This was in contrast to Opera Potentials, with one stating they hated opera . Research by Khatoon and Rehman (2021) identify a plethora of negative emotions in brand relationships, and we support this previous research by identifying the same can occur in the opera setting. Findings revealed that love was mentioned more than brand attachment; however, there were some quotes that pertained to attachment.…”
Section: Discussion: Resonance At the Operasupporting
confidence: 86%
“…This was in contrast to Opera Potentials, with one stating they hated opera . Research by Khatoon and Rehman (2021) identify a plethora of negative emotions in brand relationships, and we support this previous research by identifying the same can occur in the opera setting. Findings revealed that love was mentioned more than brand attachment; however, there were some quotes that pertained to attachment.…”
Section: Discussion: Resonance At the Operasupporting
confidence: 86%
“…Khatoon and Rehman's (2021) review on negative emotions in consumer‐brand relationships uses the PRISMA protocol and organizes the final set of 55 articles based on two frameworks: the TCM framework (i.e., theories, contexts, and methods) developed by Paul et al. (2017) and the ADE framework (i.e., antecedents, emotions, and outcomes), which is a modified version of the ADO framework (i.e., antecedents, decisions, and outcomes) devised by Paul and Benito (2018).…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…Systematic reviews can be approached in myriad ways (Paul & Criado, 2020). Theory based reviews (e.g., Gilal et al, 2019; Paul & Rosado‐Serrano, 2019) theme based reviews (e.g., Hao et al, 2021; Khatoon & Rehman, 2021; Mishra et al, 2021; Paul & Dhiman, 2021; Paul et al, 2017; Rana & Paul, 2017; Rosado‐Serrano et al, 2018), framework‐based reviews (e.g. ; Paul & Benito, 2018; Paul, Merchant, et al, 2021; Sodergren, 2021), review aiming for theory development (e.g., Paul, 2019; Paul & Mas, 2019), hybrid reviews (e.g., Dabić et al, 2020), bibliometric analysis (e.g., Ruggeri et al, 2019), and meta‐analysis (e.g., Barari et al, 2020; Rana & Paul, 2020).…”
Section: Methodsmentioning
confidence: 99%